Optimasi Tingkat Kelangsungan Hidup Ikan Ikan Kerapu Cantang Epinephelus fuscoguttatus >< Epinephelus lanceolatus Dengan Penambahan Ekstrak Daun Jambu Biji Merah Psidium guajava Linn Pada Media Transportasi - Maidah, Indah Parah; Irawan, Henky; Bakkara, Okto Rimandi (Program Studi Budidaya Perairan Universitas Maritim Raja Ali Haji, 2026)
ABSTRAK Transportation of live fish such as cantang grouper Epinephelus fuscoguttatus × Epinephelus lanceolatus is at risk of causing stress that can reduce survival rates. This study aims to determine the optimal dose of red guava leaf extract Psidium guajava Linn as a natural anesthetic to improve fish survival during transportation. This research will be conducted in December 2023 and conducted in two places, namely at Hatchery D' Marine Aquaculture and Kampung Madong. The research used a Completely Randomized Design (CRD) with four treatments, namely: K control (0 ml/L), A addition of red guava leaf extract (4 ml/L), B addition of red guava leaf extract (6 ml/L), and C addition of red guava leaf extract (8 ml/L), each with three replications. The parameters observed included survival rates after transportation and during maintenance, blood glucose levels, fish behavior, and water quality. The results showed that all treatments had a 100% survival rate after transportation. During 7 days of maintenance in floating net cages, treatment A showed the highest survival rate (100%), followed by K (86.67%), C (80%), and B (48.33%). The lowest blood glucose levels occurred in treatment B (56.67 mg/dL), while the highest was in the control (92.33 mg/dL). Fish in treatment A also showed the best behavior and feed response. These results indicate that the addition of red guava leaf extract at a dose of 4 ml/L is effective in reducing stress and increasing the survival of cantang grouper during and after transportation.